Biographical work and the production of credibility in sex work interviews. (22nd February 2022) - Gheorghiu, Iulia; Ham, Julie
Abstract: This article explores the concept of biographical work as a sustained pursuit during interviews with persons engaging in stigmatized and criminalized work. Based on interviews with women engaging in sex work and intimate economies in Hong Kong, the article examines the research interview as an interactional and institutional encounter where interviewer and interviewee jointly create meaning and articulate experiences to produce credibility. Relying on the sex workers' rights framework and its adjacent debates, the article argues that social theory and critique construct reality by shaping public discourse and moral sensitivities in institutional encounters and act as moral resources that inform positionalities. The article argues for the importance of attending to both interactional and institutional demands made by interview encounters in data interpretation.